Sero-prevalence of SARS-CoV-2 antibodies in Ethiopia: Results of the National Population Based Survey, 2021 - Geremew Tasew; Saro Abdella; Birra Bejiga; Jemal Ayalew; Masresha Tessema; Feyiso Bati; Abraham Ali; Legesse Negash; Enyew Birru; Getachew Tollera; Mohammad Ahmed; Adamu Tayachew; et al. (PLoS ONE, 2025)
Background SARS-CoV-2 pandemic has caused a continuing health crisis affecting the public health system globally. Population-based serological surveys are a highly valuable and recommended method to measure population exposure and spread of pandemic, given the existence of asymptomatic cases and little access to diagnostic testing. This national population-based study aims to estimate the seroprevalence of SARS-CoV-2 infection in all parts of Ethiopia and determine potential risk factors and burden of infection. Methods A nationwide seroprevalence survey was done among 12,756 households (HHs) across the country using three-stage stratified sampling technique from April 15, 2021 to May 16, 2021 among population of Ethiopia above 15 years of age. One member of each of the selected HHs, who fulfilled the eligibility criteria, was randomly selected. We captured data using interviews and finger prick blood samples to test for anti-SARS-CoV-2 antibodies using high specificity rapid diagnostic tests (RDTs). A questionnaire was used to capture all necessary data on demographics, social exposure, and history of vaccination for SARS-CoV-2, symptoms compatible with SARS-CoV-2, and any known medical conditions. The data were collected using an open data kits (ODK) software and imported into STATA version 17 for analysis. Descriptive statistics (frequencies and proportions) were used to summarize data on the study variables. Forest plots and maps were used to visualize the seroprevalence of SARS-CoV-2 across various individual and environmental factors. The study sample was weighted, and the survey set command in Stata (svy) was used in the analyses to account for the survey design. Adjusted Odd ratio (AOR) was used to determine higher risk factors of having been infected at least once, 95% confidence interval to assess precision of the estimates, and a P value ≤  0.05 to determine statistically significant. Result and discussion This study indicated the overall national prevalence of seropositivity was 9.3% that suggests nearly one in ten individuals in Ethiopia was exposed to SARS-CoV-2 infection by May 2021. All regional states in the country are affected with SARS-CoV-2 infection although infection was more common in densely populated regions. Seroprevalence was significantly higher among, individual, aged 35–44, 55–64 and 65 and over years had more odds of being infected by SARS-CoV-2 compared with those aged 15–24 years. The seroprevalence is also high among professional/technical occupations, and among those having at least one comorbidity. The participants who had seven and more members had higher odds of infection compared with those who had two or less members. The odds of infection among respondents, who reported having ever tested for COVID-19 and being sick since March 2020, were higher compared with their counterparts. Among the environmental factors, the odds of SARS-CoV-2 infection in urban residents were higher than in the rural setting. In relation to geographic administration boundaries, participants from Harari Region, Addis Ababa, and Benishangul Gumuz had higher odds of infection compared to those from Afar Regions respective. Conclusion and recommendations This study reveals the overall seroprevalence of SARS CoV-2 antibodies in Ethiopia was 10.0% as of May 2021. The seroprevalence of IgG antibodies against COVID-19 is higher than that of IgM antibodies, indicating a past infection. SARS-CoV-2 antibody seroprevalence was varied by regional state, sex, residence area, age, and occupational status. It also suggests that the majority of Ethiopia’s have inadequate knowledge of understanding about SARS-CoV-2 antibodies, we recommend strengthening public health and social measures to mitigate the spread of COVID-19 diseases, including increased vaccination coverage and testing capability. All responsible authorities and stakeholders working locally, nationally, and globally need to support strengthening health systems and be prepared to combat morbidity and mortality and to encourage ongoing vaccination efforts. Periodic seroprevalence surveys will aid in monitoring the status and progress of the COVID-19 pandemic.